The Role of Background Knowledge and Language Proficiency in Developing Ideas in Writing Chapter 1 of Undergraduate Thesis - Intan Husniah; Yenni Rozimela (Journal of English Language Teaching, 2023)
The knowledge possessed by someone who will write a thesis greatly influences what will be written. The difficulty of developing writing is one of the problems experienced by final year students when writing a thesis. This study focuses on the extent to which background and language skills play a role in influencing the development of writing ideas in the background to chapter 1. This research uses a qualitative method and purposive sampling involving 10 fourth year students who are writing a thesis proposal. The research location is in the English Education Study Program, Padang State University. Research results were collected through interview sessions where questions were made based on Neuman's theory (2014) and Brown's theory (2004). The results of the study show that knowledge is important before starting a thesis. So background knowledge and language skills greatly influence developing writing ideas in the background of chapter 1 of undergraduate thesis.